Correlation Analyses of Herbage Yield and Quality Components in Certain Sorghum × Sudangrass (Sorghum bicolor L.×Sorghumsudanense Staph.) Hybrid Cultivars - Serap Kızıl Aydemir; Kutalmış Turhal (Turkish Journal of Agriculture: Food Science and Technology)
The purpose of this research study was to evaluate phenotypic correlation between yield, quality and certain yield components, and to determine the direct and indirect effects of 13 different components on yield and quality in sorghum×sudangrass hybrids. The research was conducted in the trial area of the Bilecik Seyh Edebali University Faculty of Agriculture and Natural Sciences in Bilecik, Turkey, in the 2015 crop year. The randomized complete block design with 4 replications was used. In the study, Aneto and Teide sorghum×sudangrass hybrid varieties belonging to Fito Seed Company and Gözde 80, Leoti, Nes, Rox and Early Sumac sorghum×sudangrass hybrid varieties belonging to Mediterranean Agricultural Research Institute were used as the materials. Relationships between ADF (Acid Detergent Fiber) and NDF (Neutral Detergent Fiber) ratios, RFV (Relative Feed Value) and ME (Metabolic Energy) values and characters were investigated in the study, in addition to plant height, panicle height, leaf ratio, stem ratio, panicle ratio, green grass yield, hay yield and crude protein yields of sorghum×sudangrass hybrid varieties. Results show that the Teide variety showed the highest performance in terms of herbage yield, crude protein ratio, ADF, NDF, RFV and ME, while the lowest yields were obtained from Rox and Early Sumac. Crude protein ratio was found to significantly correlate with leaf ratio, ADF, NDF, RFV and ME similarly, leaf ratio correlated with ADF and NDF; ADF with NDF; RFV with leaf ratio, ADF and NDF; and ME with leaf ratio, ADF, NDF and RFV.